Some Properties of a Generalized Class of Analytic Functions Related with Janowski Functions - M. Arif; K. I. Noor; M. Raza; W. Haq (Abstract and Applied Analysis)
We define a class T̃k [A, B, α, ρ] of analytic functions by using Janowski’s functions which generalizes a number of classes studied earlier such as the class of strongly close-to-convex functions. Some properties of this class, including arc length, coefficient problems, and a distortion result, are investigated. We also discuss the growth of Hankel determinant problem.